Lean Construction in construction project management: A systematic review of theory, tools, implementation, and technology integration - Nguyễn, Minh Tự; Lê, Hoàng An; Lê, Bá Anh (Journal of Transportation Science and Technology, 2026)
The global construction industry faces persistent challenges of low productivity, material waste of 20–30% of project cost, and chronic schedule overruns. Lean Construction (LC) has emerged as a systematic production management philosophy to address these structural problems. This systematic review analyzes 90 sources on LC from 1988 to 2025 across six dimensions: (1) theoretical foundations from the Toyota Production System and Koskela’s Transformation-Flow-Value theory; (2) key tools including Last Planner System, Value Stream Mapping, and KanBIM; (3) empirical evidence from over 15 countries showing PPC improvement from 35–50% to 65–85%, 16–25% cost reduction, and 24–50% productivity increase; (4) analysis of 40 barriers across six categories and geographic regions; (5) digital technology integration encompassing 56 BIM-Lean interactions and 54 LC-IoT interactions; and (6) implications for LC application in Vietnam. Results demonstrate that LC provides a robust theoretical framework and practical tools for significant project performance improvement. Five research gaps are identified as priorities: longitudinal evidence of LC sustainability, empirical validation of LC-IoT interactions, developing-country contexts, LC-ESG linkage, and LC application in megaprojects—collectively pointing toward a Lean Construction 4.0 research agenda